The Effect of Organizational Culture and Total Quality Management on Organizational Performance by Intervening Consumer Trust: Survey of University Students and Lecturers in South Sumatra - Sakarina, Sari (International Review of Management and Marketing, 2019)
The purpose of this study was to determine the effect of organizational culture, total quality management on organizational performance by intervening consumer trust. The unit of analysis in this study is students and lecturers at Universities in South Sumatra-Indonesia. The results showed that Organizational Culture, Total Quality Management of Organizational Performance with Intervening Consumer Trust had a significant effect. The characteristics possessed by higher education institutions are in competition regarding how high the productivity of the organization is and how low the price level of the products and services offered, but more on the quality of the product or service, comfort, convenience, and accuracy and speed of achievement. Competition in the world economy of education is becoming increasingly stringent so that it demands management expertise in anticipating any changes that occur in the world of education. Furthermore, it was found that good service in student organizations and lecturers had implications for Consumer Trust as students to choose a place to study. Keywords: Organizational Culture, Total Quality Management, Organizational Performance of Consumer Trust JEL Classifications: D23, L2 DOI: https://doi.org/10.32479/irmm.8260